Three-dimensional automated breast ultrasound – a supplemental screening tool - E. A. Busko; V. V. Semiglazov; N. I. Rozhkova; S. K. Dzhahilova; E. R. Akzyanova; P. V. Krivorotko; V. V. Ryazanov; S. S. Bagnenko (Опухоли женской репродуктивной системы, 2024)
Background. Three-dimensional automated breast ultrasound (ABUS) is an innovative technology that allows global visualization of the breast and eliminates the operator-dependence of hand held ultrasound. Three-projection scanning during ABUS is provided by an ultra-long (15.4 cm) probe with a frequency of 14–16 MHz, and then the slices are reconstructed on a workstation. At the same time, high-frequency converters create high-resolution images. Through a special coronal projection, ABUS identifies variants of minimal, non-palpable breast cancer, including those with women with high mammographic breast density, which makes it a promising additional (supplemental screening) method of oncomammoscreening.Aim. To assess the use of ABUS as a supplemental screening tool in women with high mammographic breast density.Materials and methods. The study was conducted in 2018 at the N.N. Petrov National Medical Research Oncology Center, Ministry of Health of Russia. As part of the study, 192 women underwent mammography, ABUS, and multiparametric ultrasound (B-mode, color Doppler, elatography) in standard manual mode.Results. In the course of the study, in 192 patients, mammography revealed 42 cases of breast cancer, while using the AUS and manual ultrasound, additionally were identified 9 cases of breast cancer. Also, the ABUS showed high accuracy in assessment of the distribution of breast cancer – multifocal, multicentric and bilateral.Conclusion. ABUS is a promising and highly effective diagnostic method in women with high mammographic breast density, with its advantages and disadvantages, which can be used in combination with mammography as a supplemental screening tool, especially in women at high risk of developing breast cancer.